Optical Sensing of Attached Fibrinogen on Carbon Doped Titanium Surfaces. (13th April 2010) - Silvennoinen, Raimo; Vetterl, Vladimír; Hasoň, Stanislav; Silvennoinen, Martti; Myller, Kari; Vanĕk, Jiři; Cvrček, Ladislav
Abstract : The adsorption/desorption of Human Plasma fibrinogen (HPF) molecules on biosurfaces was measured in spectroscopic cuvette by a diffractive optical element- (DOE-) based sensor. To characterize the surfaces, the basic parameters as surface tension was obtained by sensing of a contact angle of water droplet and dielectric constant was measured by ellipsometry in the absence of HPF molecules. It was observed a significant correlation between the adsorption ability of HPF molecules (sensed by DOE on the basis of the changes in optical roughness (R opt ) of studied surface in the absence and presence of HPF molecules), and dielectric constant (measured by ellipsometry) of differently treated titanium surfaces, where the permittivity and dielectric loss have the known linear relation. These findings with carbon-treated biomaterial surfaces can help us to understand mechanisms behind attachment of HPF molecules on biomaterial surfaces to realize and extend variety of implants for hard tissue replacement.